2014
DOI: 10.1007/s10549-014-3018-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multifocality and multicentricity on outcome in early stage breast cancer: a systematic review and meta-analysis

Abstract: Women with multifocal or multicentric breast tumors (multifocality henceforth) have been reported to have greater probability of nodal metastasis and relapse and worse survival than women with unifocal tumors. However, these associations have been inconsistent and multifocality is not taken into account by staging guidelines and prognostic models. A systematic review of electronic databases identified publications exploring the association between multifocality and overall survival (OS), disease-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 39 publications
(67 reference statements)
5
42
0
Order By: Relevance
“…8 Burke et al reported on the experience from the Armed Forces Institute of Pathology, where they found that 43 of 167 (29%) SBNET patients had MFTs, ranging from 2–100 tumors. 16 In an autopsy series from Malmo, Sweden, the incidence of all carcinoid tumors in the population was found to be 1.22%, and 50 of 152 (33%) SBNET cases were multifocal. 10 In a study pooling data from 3 Boston hospitals, Yantiss et al reported 18 of 68 (26%) patients had MFTs, the most numerous having 30 tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 Burke et al reported on the experience from the Armed Forces Institute of Pathology, where they found that 43 of 167 (29%) SBNET patients had MFTs, ranging from 2–100 tumors. 16 In an autopsy series from Malmo, Sweden, the incidence of all carcinoid tumors in the population was found to be 1.22%, and 50 of 152 (33%) SBNET cases were multifocal. 10 In a study pooling data from 3 Boston hospitals, Yantiss et al reported 18 of 68 (26%) patients had MFTs, the most numerous having 30 tumors.…”
Section: Discussionmentioning
confidence: 96%
“…8 The etiology of multiple tumors remains unsettled, with some authors suggesting that these arise from dissemination through submucosal lymphatics, 14 and others by the development of oligoclonal tumors through field cancerization. 15 Large retrospective studies in breast and lung cancer have shown that tumor multifocality is associated with poorer prognosis, 16,17 and smaller studies in SBNETs have also suggested that multifocality may be associated with increased tumor aggressiveness. 12,13 We set out to ascertain the rate of multifocal tumors in patients with SBNETs at a single center, and determine whether patients with multifocal tumors (MFTs) had worse outcomes than patients with solitary SBNETs.…”
Section: Introductionmentioning
confidence: 99%
“…Vera-Badillo et al published in 2014 a metaanalysis of twenty-two studies, that included 67557 patients that the rate of MF/MC tumors was 9,5% (6434 patients) (7).…”
Section: Methodsmentioning
confidence: 99%
“…This wide range depends largely on the definition of MF/MC, the method used for sampling the mastectomy specimen, and the use of imaging techniques. The largest study so far (n ¼ 67,557) reported an MF/MC incidence of 9.5% [12]. Wolters et al [8] (n ¼ 8935) reported an incidence of 15.6% for MF tumors and 5.2% for MC tumors [8].…”
Section: Incidencementioning
confidence: 97%